PROGRAM BASIC UNTUK PENENTUAN BATAS ELASTIS KEKUATAN LENTUR STATIS - Suparman Kamasudirdja (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
One of the procedures for determining the elastic limit in static bending test is through eye fitting of a successive load-deflection reading with a straight line on a graph paper. The procedure is simple and does not require elaborate apparatus. Consequently, it is still applied in many testing laboratories. The above procedure however, contains some weakness, namely it is laborious, time consuming, subjective and is inconsistent within the same and among different plotters.An attempt was made by the author to use cheap personal pocket computer for finding the elastic limit of load and deflection, and hence also the corresponding modulus of elasticity and bending- strength within elastic limit. The basic programme prepared by the author, whenever needed can be used also for converting the observed load/deflection data into calibrated values or other measurement units. This could be done for example after data checking, or debugging step by inserting a jump command to a specific sub-routine which will handle specific computation